2020
DOI: 10.3892/etm.2020.9335
|View full text |Cite
|
Sign up to set email alerts
|

Reducing upper digestive bleeding risk in patients treated with direct oral anticoagulants and concomitant infection with <em>Helicobacter&nbsp;pylori</em>

Abstract: Direct oral anticoagulants (DOACs) such as apixaban or dabigatran are excellent options in preventing embolic cardiovascular events. Observational studies have shown that gastrointestinal bleeding risks produced by DOACs could be lowered when correcting some host co-factors i.e. Helicobacter pylori (HP) infection. The upper digestive bleeding (UDB) rates in patients with DOAC indication and the usefulness of anti-HP therapy addition were compared. An observational retrospective study was conducted of medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…Unlike antiplatelet therapy (platelet aggregation inhibitors), the additional influence of H. pylori on the likelihood of bleeding is generally unclear, especially in the absence of gastro-duodenal ulcers [336,337]. Nevertheless, H. pylori eradication has favourable effects on the safety of oral anticoagulant use [338]. An observational study showed lower and less complicated bleeding rates in patients where H. pylori was eradicated compared to non-eradicated patients, particularly in older patients (with previous history of peptic ulcer [339].…”
Section: Commentmentioning
confidence: 99%
“…Unlike antiplatelet therapy (platelet aggregation inhibitors), the additional influence of H. pylori on the likelihood of bleeding is generally unclear, especially in the absence of gastro-duodenal ulcers [336,337]. Nevertheless, H. pylori eradication has favourable effects on the safety of oral anticoagulant use [338]. An observational study showed lower and less complicated bleeding rates in patients where H. pylori was eradicated compared to non-eradicated patients, particularly in older patients (with previous history of peptic ulcer [339].…”
Section: Commentmentioning
confidence: 99%
“…Dennoch hat eine H. pylori-Eradikation günstige Einflüsse auf die Sicherheit des Einsatzes oraler Antikoagulanzien [337]. Eine Observationsstudie zeigte insbesondere bei älteren Patienten (und mit Historie eines peptischen Ulcus) niedrigere und weniger komplizierte Blutungsraten bei H. pylori-Eradizierten im Vergleich zu Nicht-Eradizierten [338].…”
Section: Kommentarunclassified
“…Insofern müssen Patienten mit stattgehabten Ulkusblutungen und negativem H. pylori -Testergebnis besonders konsequent auf Dauer therapiert werden. Auch bei einer Komedikation mit einem DOAK kann vermutlich das Risiko für eine Rezidivblutung durch eine Eradikationstherapie gesenkt werden 620 . Studien zu P 2 Y 12 Inhibitoren und VKA liegen zu dieser Frage nicht vor (indirekte Evidenz).…”
Section: Leitlinie – Themenkomplex 7: Nicht-helicobacter Pylori-assoz...unclassified
“…These include large ulcers, the diameter of exposed vessels, anatomical location, treatment methods, and some concomitant diseases. [5][6][7][8][9][10] Previous research has also established a variety of scoring systems in an attempt to assess the prognosis of patients more accurately. 11,12 However, the previous research results still cannot allow clinicians to perfectly predict the prognosis of patients with ulcer bleeding.…”
Section: Introductionmentioning
confidence: 99%